(untitled) (Journal of Geography and Environmental Management, 2019)
In the article an analysis of statistical characteristics of monthly sums of precipitation at the western and eastern stations of Kazakhstan for the cold period is given. The simultaneous spatial correlation between monthly sums of precipitation was assessed for the purpose of regionalization of the territory taking into account data for the last few decades.